Penggunaan Open Broadcast Software Studio dalam Mendesain Video Pembelajaran Era Pandemi - Ahmad Qorib; Husniyatus Salamah Zaniyati (STAI Syaichona Moh. Cholil Bangkalan, 2021)
This research aims to give insight to the readers, especially the teachers who make an innovative learning alternative in the epidemic which use Open Broadcast Software application base. Besides, this application makes students easier to study either real-time or recording. The research method is studies which use descriptive qualitative approach by collecting some previous studies taken from the journal which suitable with this article. The result shows that an interactive learning by using video model having a base OBS application can make the learning proses more interesting and effective, especially to the young students who have an audio visual learning style. So, the teachers who make long distance learning process by using OBS is more effective.